Remedies for breach of implied guarantess in a contract of supply of services under the Malaysian Consumer Protection Act 1999 - Amin, Naemah; Abu Bakar, Elistina (American-Eurasian Network for Scientific Information (AENSI), Jordan, 2011)
The inclusion of provisions relating to a supply of services in the Consumer protection Act 1999 (the CPA) is very significant in the development of the law of services which previously has been left behind compared to the law on sale of goods. With the main aim of protecting consumers against sub-standard, defective or ineffective services, the CPA creates a number of statutory implied guarantees. The Act also introduces an entirely different remedial scheme for breach of the guarantees which are supposed to offer new and more practical remedies to consumers. Adopting the method of content analysis, this paper focuses on examining the nature and types of remedies available for consumers in cases of services failure. It analyses the extent to which these remedies are adequate in compensating consumers’ loss, dissatisfaction or disappointment. The central of discussion is on Part IX of the CPA which deals with the rights of consumers against suppliers in respect of guarantees in the supply of services. A new regime of statutory remedies appears to be more practical and useful to the consumer particularly the right to demand the supplier to rectify the failure in the services. Nevertheless, after scrutinizing the CPA in depth, it is discovered that the remedial scheme is hampered by many limitations and is not necessarily more favourable to the consumer in all cases. The paper thus offers some recommendations to remedy the present flaws in the CPA for the betterment of consumers in Malaysia.